Update "Systemic treatment of atopic dermatitis" of the S2k‐guideline on atopic dermatitis. (25th January 2021) - Werfel, Thomas; Heratizadeh, Annice; Aberer, Werner; Ahrens, Frank; Augustin, Matthias; Biedermann, Tilo; Diepgen, Thomas; Fölster‐Holst, Regina; Kahle, Julia; Kapp, Alexander; Nemat, Katja; Peters, Eva; et al.
Summary: This guideline is an update from August 2020 the S2k‐guideline "Atopic dermatitis" published in 2015. The reason for updating this chapter of the guideline were the current developments in the field of systemic therapy of atopic dermatitis. The agreed recommendations for systemic treatment in atopic dermatitis of the present guideline are based on current scientific data. Due to the approval of dupilumab for the treatment of moderate to severe atopic dermatitis, which cannot be treated sufficiently with topical drugs alone, this part of the guideline has now been adapted and newly consented. The indication for systemic therapy and the therapeutic response to topical and systemic treatment should be recorded and documented in a suitable form in clinic and practice. A standardized documentation of the indication for system therapy in atopic dermatitis can be recommended and is also part of the updated chapter of this guideline.